A Phenomenological Study of Education for Sustainable Development in Higher Education of Pakistan - Sehrish Khan,Ayaz Muhammad Khan (PJE, 2023)
Sustainable development in higher education is still at infancy stage while the aim was to train our youth to be sustainable leaders for ensuring conservation of the environment, society and economy for future. The leading purpose of the paper was to unfold the situation of five universities for the level of embeddedness of education for sustainable development in preparing their students as sustainable leaders. The nature of the study was qualitative and phenomenological approach through semi-structured interviews (validated by four experts of related field) conducted from department heads of universities present in Lahore. Three themes (along with sub exclusive functionalities of the university) were noted during qualitative analysis of the collected data.